Ergonomics bring safety features to an aging laboratory workforce. - Gile TJ (Medical Laboratory Observer (MLO), 2009)
Regardless of the reason 'boomers' choose to stay in the lab, their managers know that having an ergonomic plan in place is especially important to the aging workforce.